2015 IEEE Conference on Computer Communications (INFOCOM) 2015
DOI: 10.1109/infocom.2015.7218393
|View full text |Cite
|
Sign up to set email alerts
|

ISP-friendly peer-assisted on-demand streaming of long duration content in BBC iPlayer

Abstract: In search of scalable solutions, CDNs are exploring P2P support. However, the benefits of peer assistance can be limited by various obstacle factors such as ISP friendlinessrequiring peers to be within the same ISP, bitrate stratificationthe need to match peers with others needing similar bitrate, and partial participation-some peers choosing not to redistribute content.This work relates potential gains from peer assistance to the average number of users in a swarm, its capacity, and empirically studies the ef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…The advantage of peer-assistance lies in the fact that peer-topeer networks are innately self-sustainable because every new user contributes an upload capacity comparable to what she has consumed from the network -a self-sustainable content swarm is able to serve most of the users' requests from fellow peers, thereby offloading traffic from content servers. Indeed, Zhao et al reports traffic savings of 70-80% in Akamai NetSession [39], and similar savings have been also suggested for BBC iPlayer (up to 88%) [18] and Conviva platform (up to 87%) [3].…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…The advantage of peer-assistance lies in the fact that peer-topeer networks are innately self-sustainable because every new user contributes an upload capacity comparable to what she has consumed from the network -a self-sustainable content swarm is able to serve most of the users' requests from fellow peers, thereby offloading traffic from content servers. Indeed, Zhao et al reports traffic savings of 70-80% in Akamai NetSession [39], and similar savings have been also suggested for BBC iPlayer (up to 88%) [18] and Conviva platform (up to 87%) [3].…”
Section: Introductionmentioning
confidence: 59%
“…), thus, measuring energy consumption as a function of the instantaneous demand. We adopted the more detailed per-bit approach in the current study because the per-session granularity of the data records we possess allows us to make fine-grain estimations of traffic demands rather than doing coarse-grain measurements based on the number of subscriptions, and also because per-user consumption patterns are highly skewed towards a small share of very active users [18]. We build on the widely used energy models of content delivery networks proposed by Valancius et al [34] and Baliga et al [6], adapting them for the peer-assisted content delivery scenario where traffic can either be delivered from active peers or from the CDN nodes if no peers are available.…”
Section: Related Papersmentioning
confidence: 99%
See 1 more Smart Citation
“…This allows for a number of new lines of exploration, particularly relating to how live videos are created and consumed by social ties. There have been a small number of studies into live streaming platforms, including Akamai [28], BBC iPlayer [15][16][17]24] or CNLive [20]. These professional platforms serve a wide range of international and professional content, although we emphasise that this differs dramatically from the user generated content discussed above.…”
Section: Background and Related Workmentioning
confidence: 99%
“…While this makes the SCORE solution specific to catch-up TV/radio, it also makes the design straightforward. Recently, we have shown that peer-assisted CDNs can also be effective for catch-up TV [24].…”
Section: Related Workmentioning
confidence: 99%